Preparation method of spherical double-layer carbon-coated lithium manganese iron phosphate positive electrode material and product thereof
Through the preparation method of spherical double-layer carbon-coated lithium manganese iron phosphate positive electrode material, the problems of poor electronic conductivity and slow lithium ion diffusion of LMFP materials are solved, and the high cycleability and rate performance of the material are achieved, which improves the electrochemical performance and commercial application potential of lithium-ion batteries.
Patent Information
- Application Number
- CN202411974534.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-31
- Publication Date
- 2025-03-21
AI Technical Summary
Lithium manganese iron phosphate (LMFP) materials have problems such as poor electronic conductivity, slow diffusion of lithium ions, manganese dissolution affects battery circulation performance and low tap density, which limits its electrochemical performance and commercial applications.
The preparation method of spherical double-layer carbon-coated lithium manganese iron phosphate positive electrode material is adopted. The morphology and structure of the material are controlled through spray drying and gel wet coating technology, ensuring that the material has a high specific surface area and double-layer carbon coating, and improving its electronic conductivity and lithium ion diffusion.
It improves the cyclability and rate performance of the material, enhances the conductivity and power density of lithium-ion batteries, and improves the thermal stability and chemical stability of the battery.
Smart Images

Figure FT_1 
Figure FT_2 
Figure FT_3
Abstract
Description
Technical Field
[0001] The invention relates to a lithium ion battery positive electrode material, and in particular to a preparation method of a spherical double-layer carbon-coated lithium manganese iron phosphate positive electrode material and a product thereof. Background Art
[0002] Lithium manganese iron phosphate (LMFP, chemical formula is LiMn 1-x Fe x Lithium iron phosphate (LFP) has attracted great attention in the market as a material for optimizing and upgrading lithium iron phosphate. This material belongs to the high-voltage phosphate series, and its voltage platform can reach 4.1V. By introducing an appropriate amount of manganese into lithium iron phosphate and adjusting the ratio of manganese to iron, lithium manganese iron phosphate has successfully improved its voltage level. The properties of lithium manganese iron phosphate are similar to those of lithium iron phosphate and lithium manganese phosphate, but it has better performance in thermal stability, chemical stability and cost-effectiveness, and its energy density has also been significantly improved. In recent years, researchers have conducted in-depth research on lithium manganese iron phosphate, and it is generally believed that the material is expected to become an ideal positive electrode material for a new generation of high-energy density power batteries.
[0003] The current problems faced by LMFP materials include poor electronic conductivity and lithium ion diffusion, manganese dissolution affecting battery cycle performance, and low tap density.
[0004] The crystal structure characteristics of LMFP lead to its low electronic conductivity and lithium ion diffusion rate. In the octahedral coordination environment, FeO6 and MnO6 octahedra lack a continuous edge-sharing network and are only connected to each other through PO4 tetrahedra, which results in poor conductivity. In addition, the PO4 tetrahedron is located between the FeO6 (MnO6) octahedra, which hinders the diffusion path of lithium ions and limits the movement of Li+ on a one-dimensional path, resulting in a lower lithium ion diffusion rate and affecting its rate performance. These limiting factors hinder the full development of the electrochemical performance of LMFP and also limit its application in a wider commercial field.
[0005] In order to improve the above-mentioned deficiencies, researchers have adopted methods such as ion doping, coating, and morphology control to improve its ion diffusion coefficient and conductivity, thereby improving its electrochemical properties such as rate and cycle. The electronic conductivity and ionic conductivity in the material and the structural stability of the material are the key factors affecting them, that is, the chemical properties of the material itself determine the main performance of the material. However, due to the anisotropy of the structure, the specific morphology of the material will also have a certain impact on its performance. Therefore, the synthesis of materials with special morphologies has certain research significance. When the material particles are spherical, the material has a very high specific surface area, which increases the reaction interface and provides more ion diffusion channels, thereby greatly improving the lithium ion diffusion coefficient and electronic conductivity of the material. Spherical materials are a very effective way to improve the power density of lithium-ion batteries. Summary of the invention
[0006] The present invention aims to provide a method for preparing a spherical double-layer carbon-coated lithium manganese iron phosphate positive electrode material.
[0007] Another object of the present invention is to provide a spherical double-layer carbon-coated lithium manganese iron phosphate positive electrode material product prepared by the above method.
[0008] The object of the present invention is achieved by the following scheme: A method for preparing a spherical double-layer carbon-coated lithium manganese iron phosphate positive electrode material comprises the following steps: (1) Take a binder, a lithium source, an iron source and a manganese source, wherein the molar amounts of the lithium source, the iron source and the manganese source are measured and proportioned according to the following chemical formula: LiMn x Fe 1-x PO4, wherein 1>x>0.1, is placed in deionized water and stirred evenly, wherein the concentration of the binder in the water is 5-25%; the solid content of the mixed solution is 30%-75%; the obtained mixed solution is spray-dried to obtain a spherical precursor; (2) calcining the obtained precursor in a tube furnace to obtain a calcined precursor; (3) mixing the calcined precursor obtained in step (2) with a carbon source to form a gel in a water bath; (4) placing the gel precursor obtained in step (3) in a tubular furnace and calcining it to obtain a spherical double-layer carbon-coated lithium manganese iron phosphate positive electrode material; The lithium source is selected from one or a combination of two or more of lithium hydroxide, lithium carbonate, lithium acetate and lithium oxalate; the iron source is selected from one or a combination of two or more of iron phosphate, iron oxalate and iron sulfate; the manganese source is selected from one or a combination of two or more of manganese carbonate, manganese acetate and manganese sulfate.
[0009] The present invention adopts a binder as a regulating agent, and after preliminary pre-sintering to obtain a carbon coating, a sol-coated elastic layer is used without destroying the spherical structure to achieve a double-layer carbon coating, thereby further improving the cyclability and rate performance of the obtained product.
[0010] In the technical solution of the present invention, starch is preferably used as a regulator with a concentration of 10 mol / L; the solid content of the solution is preferably 60%; In the technical solution of the present invention, the binder can be one or a combination of two or more selected from soluble starch, carboxymethyl cellulose and polyvinylidene fluoride.
[0011] In the technical solution of the present invention, when the mixed solution is spray-dried to prepare the precursor, the spray-drying rate is selected to be 120 mL / min.
[0012] In the technical solution described in the present invention, the lithium source is one or a combination of two or more selected from lithium hydroxide, lithium carbonate, lithium acetate and lithium oxalate; the manganese source is one or a combination of two or more selected from manganese carbonate, manganese acetate and manganese sulfate; the iron source is one or a combination of two or more selected from iron phosphate, iron sulfate and iron oxalate; the phosphorus source is one or a combination of two or more selected from phosphoric acid, diammonium phosphate and iron phosphate.
[0013] In the technical solution of the present invention, the carbon source is one or a combination of two or more selected from glucose, sucrose and carbon black.
[0014] In the technical solution of the present invention, the calcination operation is the same as the existing technology, preferably as follows: the calcination temperature of step (2) is 300-500°C for pre-calcination for 2-4 hours; the calcination temperature of step (4) is 650-850°C for short-term 6-15 hours. The temperature rise rate is 3-10°C / min.
[0015] The present invention also provides a spherical double-layer carbon-coated lithium iron manganese phosphate positive electrode material, which is prepared according to any of the methods described above. The lithium iron manganese phosphate prepared by the method described in the present invention is a double-layer carbon-coated sphere with a high specific surface area, which is conducive to the full infiltration of the electrolyte and shortens the transmission path of lithium ions, and has a high electrical conductivity, thereby effectively improving the cycle and rate performance of the obtained product.
[0016] The present invention adopts a binder as a regulating agent, and after preliminary pre-sintering to obtain a carbon coating, a sol-coated elastic layer is used without destroying the spherical structure to achieve a double-layer carbon coating, thereby further improving the cyclability and rate performance of the obtained product.
[0017] Compared with modern technology, the present invention is characterized in that: By controlling the concentration of the binder, lithium source, manganese source and iron source in water, the fluidity and viscosity of the slurry are controlled, and combined with the spraying rate, the morphology of the obtained lithium iron manganese phosphate is ensured to be spherical; The gel achieves wet coating without destroying the spherical shape of the precursor, achieving double-layer carbon coating; The method of the invention is simple, has low raw material cost and is easy to industrialize. BRIEF DESCRIPTION OF THE DRAWINGS
[0018] Figure 1 This is the XRD pattern of the spherical double-layer carbon-coated lithium manganese iron phosphate positive electrode material prepared in Example 1; like Figure 1The XRD diagram of Example 1 is shown. The diffraction peak of the material is consistent with the Li(Mn,Fe)PO4 standard card PDF#13-0336, indicating that it has an orthogonal Pnmb space group, indicating that the lithium manganese iron phosphate sample has been successfully prepared, and the sample exhibits extremely high purity and excellent crystallinity. The XRD results show that the sample synthesis is very successful and meets the predetermined assumptions. After obtaining the three materials, their electrochemical properties are comprehensively evaluated.
[0019] Figure 2 This is a CV graph of the spherical double-layer carbon-coated lithium manganese iron phosphate positive electrode material prepared in Example 1; Figure 2 The cyclic voltammetry curve of the positive electrode material of Example 2 at a scanning rate of 0.1mV / s is shown. The sample exhibits two pairs of redox peaks, corresponding to the redox reactions of Fe3+ / Fe2+ and Mn3+ / Mn2+, respectively, accompanied by the extraction and embedding process of lithium ions in the olivine structure positive electrode material. The lithium manganese iron phosphate positive electrode material has two pairs of symmetrical and sharp redox peaks, which shows that the positive electrode material not only has a high Fe3+ / Fe2+ peak current, but also has a high Mn3+ / Mn2+ peak current. Therefore, the synthesized material has a faster lithium ion extraction and embedding rate and better kinetic characteristics of Mn3+ / Mn2+ mutual conversion during the redox process. The synthesized material not only has a stronger redox peak current intensity, but also a smaller voltage gap between the redox peaks.
[0020] Figure 3 This is a rate performance diagram of a battery assembled using the spherical double-layer carbon-coated lithium manganese iron phosphate prepared in Example 1 as the positive electrode material.
[0021] like Figure 3 As shown, from the rate performance diagram of Example 1, it can be seen that its 0.1C specific capacity is nearly 155 mAh g-1, the 10C specific capacity is 75 mAh g-1, and the 0.1C specific capacity is 136 mAh g-1, showing excellent rate performance. DETAILED DESCRIPTION
[0022] The present invention is further described in detail below in conjunction with specific embodiments to provide a better understanding of the content of the present invention, but the present invention is not limited to the following examples.
[0023] Example 1 A spherical double-layer carbon-coated lithium manganese iron phosphate positive electrode material is prepared according to the following steps: 1) Dissolve soluble starch in 500 ml of deionized water to obtain a solution with a starch concentration of 10 mol / L, then add lithium carbonate, iron phosphate, and manganese carbonate, wherein Li:Fe:Mn:P=1:0.4:0.6:1, solid content 60 wt%, magnetic stirring at room temperature for 3 h, rotation speed 500 r / min, to obtain a mixed solution; the obtained mixed solution is spray dried in a spray drying tower at a rate of 10 ml / min, the inlet temperature is set to 210°C, and the outlet temperature is set to 120°C, to obtain a light green lithium iron manganese phosphate precursor; 2) The obtained light green lithium nickel manganese oxide precursor was placed in a tube furnace and calcined at 350°C for 3 hours at a heating rate of 7°C / min to obtain a calcined precursor; 3) the calcined precursor obtained in 2) and glucose are added into deionized water at a mass ratio of 95:5 to form a gel; 4) The gel obtained in 3) was placed in a tubular furnace and calcined at 750°C for 12 h with a heating rate of 8°C / min. The furnace was cooled to obtain a black powder material, which was ground to obtain a double-layer carbon-coated spherical lithium manganese iron phosphate positive electrode material.
[0024] The XRD pattern of the double-layer carbon-coated spherical lithium manganese iron phosphate positive electrode material is as follows: Figure 1 As shown, the diffraction peak of the material is consistent with the Li(Mn,Fe)PO4 standard card PDF#13-0336, indicating that it has an orthorhombic Pnmb space group, indicating that the lithium manganese iron phosphate sample has been successfully prepared, and the sample shows extremely high purity and excellent crystallinity. The XRD results show that the sample synthesis is very successful and meets the predetermined assumptions. After obtaining the three materials, their electrochemical properties were comprehensively evaluated.
[0025] Battery assembly: Lithium iron manganese phosphate, acetylene black and PVDF were weighed in a ratio of 8:1:1, and after thorough grinding, 1 ml of NMP was added to disperse them evenly. After slurry preparation, the slurry was evenly coated on aluminum foil to make a positive electrode sheet. In a glove box filled with argon, a metal lithium sheet was used as the counter electrode, Celgard 2400 was used as the diaphragm, and 1 mol / L LiPF6 / EC:DEC (volume ratio of 1:1) was used as the electrolyte to assemble a CR2032 button battery.
[0026] The battery capacity is measured in the voltage range of 2.8-4.8V, and the 1C cycle data is as follows: Figure 1 As shown, the first discharge specific capacity of 1C is 128mAh / g.
[0027] The rate performance diagram is as follows: Figure 3As shown, its 0.1C specific capacity is nearly 155 mAh g-1, the 10C specific capacity is 75 mAh g-1, and the 0.1C specific capacity is 136 mAh g-1, showing excellent rate performance.
[0028] Example 2 A spherical double-layer carbon-coated lithium manganese iron phosphate positive electrode material is prepared by the following steps except step 1) and the remaining steps are the same as those in Example 1: 1) Dissolve soluble starch in 500 ml of deionized water to obtain a starch solution with a concentration of 5 mol / L, then add lithium carbonate, iron phosphate and manganese carbonate, wherein Li:Fe:Mn:P=1:0.4:0.6:1 and the solid content is 40 wt%; stir magnetically at room temperature for 3 h at a speed of 500 r / min to obtain a mixed solution; spray dry the obtained mixed solution in a spray drying tower at a rate of 10 ml / min, set the inlet temperature to 210° C. and the outlet temperature to 120° C. to obtain a light green lithium iron manganese phosphate precursor; 2) The obtained light green lithium nickel manganese oxide precursor was placed in a tube furnace and calcined at 350°C for 3 hours at a heating rate of 7°C / min to obtain a calcined precursor; 3) the calcined precursor obtained in 2) and glucose are added into deionized water at a mass ratio of 95:5 to form a gel; 4) The gel obtained in 3) was placed in a tubular furnace and calcined at 750°C for 12 h with a heating rate of 8°C / min. The furnace was cooled to obtain a black powder material, which was ground to obtain a double-layer carbon-coated spherical lithium manganese iron phosphate positive electrode material.
[0029] The cyclic voltammetry curve of the obtained positive electrode material at a scan rate of 0.1mV / s is shown in Figure 2 As shown, the sample exhibits two pairs of redox peaks, corresponding to Fe 3+ / Fe 2+ With Mn 3+ / Mn 2+ The redox reaction is accompanied by the extraction and insertion of lithium ions in the olivine structure cathode material. The lithium manganese iron phosphate cathode material has two pairs of symmetrical and sharp redox peaks, which shows that the cathode material not only has high Fe 3+ / Fe 2+ peak current, and has high Mn 3+ / Mn 2+ Therefore, the synthesized material has a faster lithium ion extraction and insertion rate and better Mn 3+ / Mn 2+ The resulting material not only has a stronger redox peak current intensity, but also a smaller voltage gap between redox peaks.
[0030] The assembly and performance test of the battery are the same as in Example 1.
[0031] Example 3 A spherical double-layer carbon-coated lithium manganese iron phosphate positive electrode material is prepared by the following steps except step 1) and the remaining steps are the same as those in Example 1: 1) Dissolve soluble starch in 350 ml of deionized water to obtain a starch solution with a concentration of 15 mol / L, then add lithium carbonate, iron phosphate and manganese carbonate, wherein Li:Fe:Mn:P=1:0.4:0.6:1, and the solid content is 70 wt%; stir magnetically at room temperature for 3 h at a speed of 300 r / min to obtain a mixed solution; spray dry the obtained mixed solution in a spray drying tower at a rate of 10 ml / min, set the inlet temperature to 210° C., and the outlet temperature to 120° C., to obtain a light green lithium iron manganese phosphate precursor; 2) The obtained light green lithium nickel manganese oxide precursor was placed in a tube furnace and calcined at 350°C for 3 hours at a heating rate of 7°C / min to obtain a calcined precursor; 3) the calcined precursor obtained in 2) and glucose are added into deionized water at a mass ratio of 95:5 to form a gel; 4) The gel obtained in 3) was placed in a tubular furnace and calcined at 750°C for 12 h with a heating rate of 8°C / min. The furnace was cooled to obtain a black powder material, which was ground to obtain a double-layer carbon-coated spherical lithium manganese iron phosphate positive electrode material.
[0032] The assembly and performance test of the battery are the same as in Example 1. Comparative Example 1 A lithium manganese iron phosphate positive electrode material, without subsequent steps 3) and 4), the remaining steps are the same as those in Example 1, and is prepared according to the following steps: 1) Take a certain mass of soluble starch and dissolve it in 500 ml of deionized water to obtain a starch solution concentration of 10 mol / L, then add lithium carbonate, iron phosphate and manganese carbonate, wherein Li:Fe:Mn:P=1:0.4:0.6:1, and the solid content is 60wt%; magnetic stirring is performed at room temperature for 3 hours at a speed of 500 r / min to obtain a mixed solution; the obtained mixed solution is spray dried in a spray drying tower at a rate of 10 ml / min, and the inlet temperature is set to 210°C and the outlet temperature is set to 120°C to obtain a lithium iron manganese phosphate precursor; 2) The obtained light green lithium nickel manganese oxide precursor is placed in a tube furnace and calcined. The calcination procedure is as follows: calcination at 650 degrees Celsius for 12 hours with a heating rate of 8 degrees Celsius / min to obtain a calcined precursor.
[0033] Comparative Example 2 A lithium manganese iron phosphate positive electrode material is prepared according to the following steps, except for step 1), and the remaining steps are the same as those in Example 1: 1) Take a certain mass of soluble starch and dissolve it in 500 ml of deionized water to obtain a starch solution concentration of 10 mol / L, then add lithium carbonate, iron phosphate and manganese carbonate, wherein Li:Fe:Mn:P=1:0.4:0.6:1, solid content 60wt%, and adjust the solid content to 20wt%; magnetic stirring at room temperature for 3 hours at a speed of 500r / min to obtain a mixed solution; the obtained mixed solution is spray dried in a spray drying tower at a rate of 10 ml / min, and the inlet temperature is set to 210°C and the outlet temperature is set to 120°C to obtain a light green lithium iron manganese phosphate precursor; 2) The obtained light green lithium nickel manganese oxide precursor was placed in a tube furnace and calcined at 350°C for 3 hours at a heating rate of 7°C / min to obtain a calcined precursor; 3) the calcined precursor obtained in 2) and glucose are added into deionized water at a mass ratio of 95:5 to form a gel; 4) The gel obtained in 3) was placed in a tubular furnace and calcined at 750°C for 12 h with a heating rate of 8°C / min. The furnace was cooled to obtain a black powder material, which was ground to obtain a double-layer carbon-coated spherical lithium manganese iron phosphate positive electrode material.
[0034] Comparative Example 3 A lithium manganese iron phosphate positive electrode material is prepared according to the following steps, except that the solid content in step 1) is different, and the remaining steps are the same as those in Example 1: 1) Take a certain amount of soluble starch and dissolve it in 500ml of deionized water (concentration is 10mol / L), then add a certain proportion of lithium carbonate, iron phosphate, and manganese carbonate (adjust the solid content to 70wt%). Stir magnetically at room temperature for 3h at a speed of 500r / min to obtain a mixed solution; spray dry the obtained mixed solution in a spray drying tower at a rate of 10ml / min, set the inlet temperature to 210℃, and the outlet temperature to 120℃ to obtain a light green lithium iron manganese phosphate precursor; 2) The obtained light green lithium nickel manganese oxide precursor was placed in a tube furnace and calcined at 350°C for 3 hours at a heating rate of 7°C / min to obtain a calcined precursor; 3) the calcined precursor obtained in 2) and glucose are added into deionized water at a mass ratio of 95:5 to form a gel; 4) The gel obtained in 3) was placed in a tubular furnace and calcined at 750°C for 12 h with a heating rate of 8°C / min. The furnace was cooled to obtain a black powder material, which was ground to obtain a double-layer carbon-coated spherical lithium manganese iron phosphate positive electrode material.
[0035] As shown in Table 1, the lithium-ion battery prepared by the spherical double-layer carbon-coated lithium manganese iron phosphate nano-positive electrode material obtained in the present invention exhibits good electrochemical performance. The lithium-ion battery prepared by the nano-lithium manganese iron phosphate obtained in Example 1 has a room temperature first charge specific capacity of 154.8 mAh g-1 and a first discharge specific capacity of 134.1 mAh g-1. -1 .
Claims
1. A method for preparing a spherical double-layer carbon-coated lithium manganese iron phosphate positive electrode material, characterized in that: The following steps are involved: (1) Take a binder, a lithium source, an iron source and a manganese source, wherein the molar amounts of the lithium source, the iron source and the manganese source are measured and proportioned according to the following chemical formula: LiMn x Fe 1-x PO4, wherein 1>x>0.1, is placed in deionized water and stirred evenly, wherein the concentration of the binder in the water is 5-25%; the solid content of the mixed solution is 30%-75%; the obtained mixed solution is spray-dried to obtain a spherical precursor; (2) calcining the obtained precursor in a tube furnace to obtain a calcined precursor; (3) mixing the calcined precursor obtained in step (2) with a carbon source to form a gel in a water bath; (4) placing the gel precursor obtained in step (3) in a tubular furnace and calcining it to obtain a spherical double-layer carbon-coated lithium manganese iron phosphate positive electrode material; The lithium source is selected from one or a combination of two or more of lithium hydroxide, lithium carbonate, lithium acetate and lithium oxalate; the iron source is selected from one or a combination of two or more of iron phosphate, iron oxalate and iron sulfate; the manganese source is selected from one or a combination of two or more of manganese carbonate, manganese acetate and manganese sulfate.
2. The method for preparing the spherical double-layer carbon-coated lithium manganese iron phosphate positive electrode material according to claim 1, characterized in that: The binder is one or a combination of two or more selected from soluble starch, carboxymethyl cellulose and polyethylene glycol.
3. The method for preparing the spherical double-layer carbon-coated lithium manganese iron phosphate positive electrode material according to claim 1, characterized in that: The rate during spray drying was 30-120 mL / min.
4. The method for preparing the spherical double-layer carbon-coated lithium manganese iron phosphate positive electrode material according to claim 1, characterized in that: The carbon source is one or a combination of two or more of glucose, sucrose and carbon black.
5. The method for preparing the spherical double-layer carbon-coated lithium manganese iron phosphate positive electrode material according to claim 1, characterized in that: The phosphorus source is one or a combination of two or more selected from phosphoric acid, ammonium dihydrogen phosphate and ferric phosphate.
6. The method for preparing the spherical double-layer carbon-coated lithium manganese iron phosphate positive electrode material according to any one of claims 1 to 5, characterized in that: Prepare as follows: 1) Dissolve soluble starch in 500 ml of deionized water to obtain a solution with a starch concentration of 10 mol / L, then add lithium carbonate, iron phosphate, and manganese carbonate, wherein Li:Fe:Mn:P=1:0.4:0.6:1, solid content 60 wt%, magnetic stirring at room temperature for 3 h, rotation speed 500 r / min, to obtain a mixed solution; the obtained mixed solution is spray dried in a spray drying tower at a rate of 10 ml / min, the inlet temperature is set to 210°C, and the outlet temperature is set to 120°C, to obtain a light green lithium iron manganese phosphate precursor; 2) The obtained light green lithium nickel manganese oxide precursor was placed in a tube furnace and calcined at 350° C. for 3 h at a heating rate of 7° C. / min to obtain a calcined precursor; 3) the calcined precursor obtained in 2) and glucose are added into deionized water at a mass ratio of 95:5 to form a gel; 4) The gel obtained in 3) was placed in a tubular furnace and calcined at 750°C for 12 h with a heating rate of 8°C / min. The furnace was cooled to obtain a black powder material, which was ground to obtain a double-layer carbon-coated spherical lithium manganese iron phosphate positive electrode material.
7. The method for preparing the spherical double-layer carbon-coated lithium manganese iron phosphate positive electrode material according to any one of claims 1 to 5, characterized in that: Prepare as follows: 1) Dissolve soluble starch in 500 ml of deionized water to obtain a starch solution with a concentration of 5 mol / L, then add lithium carbonate, iron phosphate and manganese carbonate, wherein Li:Fe:Mn:P=1:0.4:0.6:1 and the solid content is 40 wt%; stir magnetically at room temperature for 3 h at a speed of 500 r / min to obtain a mixed solution; spray dry the obtained mixed solution in a spray drying tower at a rate of 10 ml / min, set the inlet temperature to 210° C. and the outlet temperature to 120° C. to obtain a light green lithium iron manganese phosphate precursor; 2) The obtained light green lithium nickel manganese oxide precursor was placed in a tube furnace and calcined at 350° C. for 3 h at a heating rate of 7° C. / min to obtain a calcined precursor; 3) the calcined precursor obtained in 2) and glucose are added into deionized water at a mass ratio of 95:5 to form a gel; 4) The gel obtained in 3) was placed in a tubular furnace and calcined at 750°C for 12 h with a heating rate of 8°C / min. The furnace was cooled to obtain a black powder material, which was ground to obtain a double-layer carbon-coated spherical lithium manganese iron phosphate positive electrode material.
8. The method for preparing the spherical double-layer carbon-coated lithium manganese iron phosphate positive electrode material according to any one of claims 1 to 5, characterized in that: Prepare as follows: 1) Dissolve soluble starch in 350 ml of deionized water to obtain a starch solution with a concentration of 15 mol / L, then add lithium carbonate, iron phosphate and manganese carbonate, wherein Li:Fe:Mn:P=1:0.4:0.6:1, and the solid content is 70 wt%; stir magnetically at room temperature for 3 h at a speed of 300 r / min to obtain a mixed solution; spray dry the obtained mixed solution in a spray drying tower at a rate of 10 ml / min, set the inlet temperature to 210° C., and the outlet temperature to 120° C., to obtain a light green lithium iron manganese phosphate precursor; 2) The obtained light green lithium nickel manganese oxide precursor was placed in a tube furnace and calcined at 350° C. for 3 h at a heating rate of 7° C. / min to obtain a calcined precursor; 3) the calcined precursor obtained in 2) and glucose are added into deionized water at a mass ratio of 95:5 to form a gel; 4) The gel obtained in 3) was placed in a tubular furnace and calcined at 750°C for 12 h with a heating rate of 8°C / min. The furnace was cooled to obtain a black powder material, which was ground to obtain a double-layer carbon-coated spherical lithium manganese iron phosphate positive electrode material.
9. A spherical lithium-ion battery positive electrode material, lithium manganese iron phosphate, characterized in that Prepared according to any one of claims 1-8; the prepared lithium manganese iron phosphate is a double-layer carbon-coated sphere with a high specific surface area, which is conducive to the full infiltration of the electrolyte and shortens the transmission path of lithium ions, and has a high electrical conductivity, thereby effectively improving the cycle and rate performance of the obtained product.